2019
DOI: 10.1051/e3sconf/201911600055
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the performance of a small counter-rotating wind turbine

Abstract: The article presents results of the investigation on the performance of a small counter-rotating wind turbine. Wind turbine has been simulated using Computational Fluid Dynamics methods. Actuator Line Model has been successfully used to represent rotors in computational domain. Parametric study has been carried out, taking into account changes in the tip speed ratio of the rotors while maintaining a constant distance between upwind and downwind rotor. Study results revealed noticeable increase in power coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Cluster where simulation have been carried out is based on Intel ® Xeon ® Processor E5 v3 @ 2, 3 GHz. In the previous papers [32,33], authors presented partial simulations results obtained with proposed approach while in the present one full parametric study results are described.…”
Section: Crwt Parametric Studymentioning
confidence: 99%
“…Cluster where simulation have been carried out is based on Intel ® Xeon ® Processor E5 v3 @ 2, 3 GHz. In the previous papers [32,33], authors presented partial simulations results obtained with proposed approach while in the present one full parametric study results are described.…”
Section: Crwt Parametric Studymentioning
confidence: 99%
“…Pacholczyk et al (2017) demonstrated by simulation that a counterrotating 5 MW wind turbine brings approximately 20% of additional power compared to the conventional type. Other results refer to the performance of counter-rotating WECS at different aerodynamic loads and blade pitch angles (Jung et al, 2005;No et al, 2009;Rosenberg et al, 2014;Blecharz and Pacholczyk, 2018;Wang et al, 2022), for different number of blades (Pamuji and Bramantya, 2019), various rotor axial distances (Irawan and Bramantya, 2016;Koehuan and SugiyonoKamal, 2017;Pacholczyk et al, 2019), or different rotor configurations (Radhakrishnan et al, 2022). Thus, Rosenberg et al (2014) demonstrated that the power coefficient for counter-rotating rotors is influenced by the distance between the rotors and their diameters, increasing by 8%-9% when the distance equals the rotor radius and by 7% when the diameter of the upwind rotor is a quarter of the downwind rotor diameter.…”
mentioning
confidence: 99%